Contribution and effectiveness of ski and pole forces in selected roller skiing techniques on treadmill at moderate inclines - Zhao, Shuang; Lindinger, Stefan; Ohtonen, Olli; Linnamo, Vesa (Frontiers in Sports and Active Living, 2023)
Background: Most of the studies about the effects of incline on cross-country skiing are related to the metabolic efficiency. The effective skiing biomechanics has also been indicated to be among the key factors that may promote good performance. The aims of this study were to provide biomechanical characteristics and investigate the relative contribution and effectiveness of ski and pole forces in overcoming the total external resistance with double poling (DP) and Gear 3 (G3) techniques at varying moderate uphill inclines. Methods: 10 male cross-country skiers participated in this study. Custom-made force measurement bindings, pole force sensors, and an 8-camera Vicon system were used to collect force data and ski and pole kinematics at 3°, 4° and 5° with 10 km/h skiing speed. Results: The cycle length decreased by 10% and 7% with DP and G3 technique from 3° to 5° (p < 0.001, p < 0.001). The cycle rate (CR) increased by 13% and 9% from 3° to 5° with DP and G3 technique respectively. From 3° to 5°, the peak pole force increased by 25% (p < 0.001) and 32% (p < 0.001) with DP and G3 technique. With DP technique, the average cycle propulsive force (ACPF) increased by 46% (p < 0.001) from 3°to 5°and with G3 technique, the enhancement for ACPF was 50% (p < 0.001). In G3 technique, around 85% was contributed by poles in each incline. Conclusion: The higher power output in overcoming the total resistance was required to ski at a greater incline. With DP technique, the upper body demands and technical effectiveness were increasing with incline. With G3 technique, the role of external pole work for propulsion is crucial over different terrains while role of legs may stay more in supporting the body against gravity and repositioning body segments.